Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

3xx+x\left(-8\right)-14=2
Variable x cannot be equal to 0 since division by zero is not defined. Multiply both sides of the equation by x.
3x^{2}+x\left(-8\right)-14=2
Multiply x and x to get x^{2}.
3x^{2}+x\left(-8\right)-14-2=0
Subtract 2 from both sides.
3x^{2}+x\left(-8\right)-16=0
Subtract 2 from -14 to get -16.
3x^{2}-8x-16=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-8\right)±\sqrt{\left(-8\right)^{2}-4\times 3\left(-16\right)}}{2\times 3}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 3 for a, -8 for b, and -16 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-8\right)±\sqrt{64-4\times 3\left(-16\right)}}{2\times 3}
Square -8.
x=\frac{-\left(-8\right)±\sqrt{64-12\left(-16\right)}}{2\times 3}
Multiply -4 times 3.
x=\frac{-\left(-8\right)±\sqrt{64+192}}{2\times 3}
Multiply -12 times -16.
x=\frac{-\left(-8\right)±\sqrt{256}}{2\times 3}
Add 64 to 192.
x=\frac{-\left(-8\right)±16}{2\times 3}
Take the square root of 256.
x=\frac{8±16}{2\times 3}
The opposite of -8 is 8.
x=\frac{8±16}{6}
Multiply 2 times 3.
x=\frac{24}{6}
Now solve the equation x=\frac{8±16}{6} when ± is plus. Add 8 to 16.
x=4
Divide 24 by 6.
x=-\frac{8}{6}
Now solve the equation x=\frac{8±16}{6} when ± is minus. Subtract 16 from 8.
x=-\frac{4}{3}
Reduce the fraction \frac{-8}{6} to lowest terms by extracting and canceling out 2.
x=4 x=-\frac{4}{3}
The equation is now solved.
3xx+x\left(-8\right)-14=2
Variable x cannot be equal to 0 since division by zero is not defined. Multiply both sides of the equation by x.
3x^{2}+x\left(-8\right)-14=2
Multiply x and x to get x^{2}.
3x^{2}+x\left(-8\right)=2+14
Add 14 to both sides.
3x^{2}+x\left(-8\right)=16
Add 2 and 14 to get 16.
3x^{2}-8x=16
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{3x^{2}-8x}{3}=\frac{16}{3}
Divide both sides by 3.
x^{2}-\frac{8}{3}x=\frac{16}{3}
Dividing by 3 undoes the multiplication by 3.
x^{2}-\frac{8}{3}x+\left(-\frac{4}{3}\right)^{2}=\frac{16}{3}+\left(-\frac{4}{3}\right)^{2}
Divide -\frac{8}{3}, the coefficient of the x term, by 2 to get -\frac{4}{3}. Then add the square of -\frac{4}{3} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-\frac{8}{3}x+\frac{16}{9}=\frac{16}{3}+\frac{16}{9}
Square -\frac{4}{3} by squaring both the numerator and the denominator of the fraction.
x^{2}-\frac{8}{3}x+\frac{16}{9}=\frac{64}{9}
Add \frac{16}{3} to \frac{16}{9} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x-\frac{4}{3}\right)^{2}=\frac{64}{9}
Factor x^{2}-\frac{8}{3}x+\frac{16}{9}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-\frac{4}{3}\right)^{2}}=\sqrt{\frac{64}{9}}
Take the square root of both sides of the equation.
x-\frac{4}{3}=\frac{8}{3} x-\frac{4}{3}=-\frac{8}{3}
Simplify.
x=4 x=-\frac{4}{3}
Add \frac{4}{3} to both sides of the equation.